Carbon-ceramic composite material sagger and preparation method thereof
By using carbon ceramic composite materials and silicon carbide coating technology, the problem of graphite cassette voids being easily damaged in high temperature environments is solved, the mechanical properties and service life of the cassette are significantly improved, and a more environmentally friendly and economical production process is achieved.
Patent Information
- Application Number
- CN202411799197.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
Existing graphite cassettes are easily damaged in high temperature environments, have low structural strength, short service life, and have problems of polluting the environment during production.
The cassette is prepared using carbon ceramic composite material, and the cassette is preformed by mold cutting and needle puncture, followed by chemical vapor deposition, resin impregnation and curing, carbonization and graphitization, and finally the surface is coated with a silicon carbide coating.
The compressive strength, bending strength, wear resistance, high temperature resistance and oxidation resistance of the silhouette are improved, the service life is extended, the production cost is reduced, and the frequency of the silhouette is reduced.
Smart Images

Figure BDA0005177601760000071 
Figure BDA0005177601760000081 
Figure HDA0005177601770000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon-carbon composite material applications, and in particular to a carbon-ceramic composite material sagger and a preparation method thereof. Background Art
[0002] In the lithium-ion battery manufacturing industry, negative electrode saggers are mainly used to load and sinter negative electrode materials. Saggers are containers mainly made of graphite or other high-temperature resistant materials. Their main function is to carry and protect the negative electrode active material from contamination during the sintering process in a high-temperature environment, thereby ensuring the quality and performance of the negative electrode material.
[0003] In the lithium battery manufacturing process, the negative electrode materials (such as graphite, silicon-based materials, etc.) need to be placed in a sagger and sintered at a specific temperature after mixing, granulating, and pressing, so that the active substances are fully integrated with the conductive agent, binder and other components to form a stable negative electrode sheet structure.
[0004] At present, graphite saggers have the disadvantages of low strength, short life and environmental pollution during the production process. Frequent rapid cooling and heating or mechanical shock may cause structural damage and shorten the service life of the graphite sagger. Based on the above problems, it is necessary to provide a new sagger to overcome the above defects as much as possible. Summary of the invention
[0005] The present application provides a carbon-ceramic composite material sagger and a preparation method thereof. The carbon-ceramic composite material sagger prepared by the preparation method of the present application has excellent compressive strength, bending strength, wear resistance, high temperature resistance and oxidation resistance. Compared with the graphite sagger, the carbon-ceramic composite material sagger provided by the present application has a longer service life.
[0006] In the first aspect, the present application provides a method for preparing a carbon-ceramic composite material sagger, using the following technical solution:
[0007] A method for preparing a carbon-ceramic composite material sagger, the preparation method specifically comprising the following steps:
[0008] Based on the mold, the pre-compounded plain carbon cloth and carbon fiber mesh are cut, laid layer by layer, and needled layer by layer to form a sagger preform; the density of the sagger preform is 0.4-0.6g / cm 3 ; The density of the plain carbon cloth is 300-500g / m 2 The density of the carbon fiber mesh is 50-200g / m 2 ;
[0009] After the needle punching is completed, the mold is removed and the curing treatment is performed to obtain a sagger preform embryo, and the sagger preform embryo is densified by chemical vapor deposition; the density of the sagger preform embryo after densification is 1.2-1.3g / cm3 ;
[0010] Continue to perform resin impregnation, curing and carbonization treatment on the sagger preform embryo; after treatment, the density of the sagger preform embryo is 1.4-1.5g / cm 3 ;
[0011] Then, the sagger preform embryo is subjected to graphitization treatment;
[0012] The silicon carbide mixture is used to evenly apply a silicon carbide coating on the surface of the sagger preform embryo, and the coating is vapor deposited to obtain a finished product with a uniform silicon carbide coating on the surface, that is, a carbon-ceramic composite material sagger.
[0013] The present application prepares a sagger preform body by needle punching carbon cloth and mesh tire into the sagger preform body, and then subjecting the sagger preform body to chemical vapor deposition, impregnation carbonization, and high-temperature graphitization treatment, and finally applying silicon carbide coating on the surface of the sagger preform body and subjecting the sagger preform body to vapor deposition treatment, thereby finally obtaining the finished product.
[0014] The carbon-ceramic composite material sagger prepared by the preparation method provided in the present application has both the excellent mechanical properties of the carbon-carbon composite material and the oxidation resistance of the silicon carbide coating. Compared with the graphite sagger, the sagger prepared by the preparation method provided in the present application has better compressive strength, bending strength, wear resistance and oxidation resistance. In particular, it can better maintain structural stability under high temperature environment and is not easy to deform and crack.
[0015] At the same time, the lightweight design of the carbon-ceramic composite material sagger allows the wall thickness to be thinned, which means that in the same volume, more materials can be accommodated for sintering, thereby improving production capacity and work efficiency. This is due to its superior high temperature resistance and oxidation resistance. Therefore, the overall service life of the sagger prepared by the preparation method provided by the present application is generally longer than that of the traditional graphite sagger, which not only reduces the replacement frequency of the sagger, but also reduces the production cost.
[0016] The present application overcomes the difficulty of the complicated needle punching of square carbon fiber preforms, and at the same time realizes the silicon carbide anti-oxidation coating on the surface of the square carbon-carbon composite material, which greatly prolongs the service life of the sagger. The original service life of the graphite sagger is 10-12 months, while the service life of the carbon-ceramic composite material sagger provided by the present application can reach 20-24 months, which is more than doubled.
[0017] Optionally, the silicon carbide mixture is prepared by uniformly mixing silicon carbide particles and epoxy resin in a weight ratio of (0.5-1):(0.5-1).
[0018] Optionally, the particle size of the silicon carbide particles is ≥200 mesh.
[0019] Optionally, the epoxy resin has a carbon residue rate of ≤30% and a viscosity of 100-280 mPa·s.
[0020] Optionally, the temperature of the vapor deposition coating is 1000-1100° C., and the insulation time is 250-300 hours.
[0021] Optionally, the acupuncture sequence is bottom, bottom arc, straight segment and straight segment arc.
[0022] Optionally, the bottom and the bottom arc are punctured with a depth of 12-16 mm and a density of 12-25 needles / cm 2 Staggered acupuncture.
[0023] Optionally, the straight segment and the straight segment arc are needled at a depth of 14-18 mm and a density of 12-25 needles / cm 2 Staggered acupuncture.
[0024] Optionally, the curing treatment temperature is 250-300° C., and the insulation time is 4-8 hours.
[0025] Optionally, the temperature of the chemical vapor deposition is 1000-1100° C., and the holding time is 250-300 h.
[0026] Optionally, the temperature of the graphitization treatment is 1800-2100° C., and the insulation time is 5-10 h.
[0027] In a second aspect, the present application also provides a carbon-ceramic composite material sagger produced using the above-mentioned preparation method.
[0028] In summary, the present application includes at least one of the following beneficial technical effects:
[0029] The carbon-ceramic composite material sagger prepared by the preparation method of the present application has excellent compressive strength, flexural strength, wear resistance, high temperature resistance and oxidation resistance. Compared with the graphite sagger, the carbon-ceramic composite material sagger provided by the present application has a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A carbon-ceramic composite material sagger prepared by the preparation method provided in the present application. DETAILED DESCRIPTION
[0031] Before describing the embodiments of the present application in detail, it should be understood that the terms used herein are only used for the purpose of describing specific embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by ordinary technicians in the field to which the terms belong.
[0032] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0034] The present application provides a method for preparing a carbon-ceramic composite material sagger and a carbon-ceramic composite material sagger prepared by the preparation method.
[0035] The preparation method of the carbon-ceramic composite material sagger specifically comprises the following steps:
[0036] Based on the mold, the pre-compounded plain carbon cloth and carbon fiber mesh are cut, laid layer by layer, and needled layer by layer to form a sagger preform; the density of the sagger preform is 0.4-0.6g / cm 3 ;
[0037] After the needle punching is completed, the mold is removed and the curing treatment is performed to obtain a sagger preform embryo, and the sagger preform embryo is densified by chemical vapor deposition; the density of the sagger preform embryo after densification is 1.2-1.3g / cm 3 ;
[0038] Continue to perform resin impregnation, curing and carbonization treatment on the sagger preform embryo; after treatment, the density of the sagger preform embryo is 1.4-1.5g / cm 3 ;
[0039] Then, the sagger preform embryo is subjected to graphitization treatment;
[0040] The silicon carbide mixture is used to evenly apply a silicon carbide coating on the surface of the sagger preform embryo, and the coating is vapor deposited to obtain a finished product with a uniform silicon carbide coating on the surface, that is, a carbon-ceramic composite material sagger.
[0041] In a specific embodiment, the preparation method provided in the present application specifically comprises the following steps:
[0042] (1) Based on the mold, the pre-compounded plain carbon cloth and carbon fiber mesh are cut, laid layer by layer, and needled layer by layer to form a sagger preform; the density of the sagger preform is 0.4-0.6g / cm 3 .
[0043] The sequence of acupuncture is bottom, bottom arc, straight segment and straight segment arc.
[0044] Among them, the density of plain carbon cloth is 300-500g / m 2 ;The density of carbon fiber mesh is 50-200g / m 2 .
[0045] The bottom and bottom arc adopt acupuncture depth of 12-16mm and acupuncture density of 12-25 needles / cm 2 Staggered acupuncture.
[0046] The straight segment and the straight segment arc adopt the needling depth of 14-18mm and the needling density of 12-25 needles / cm 2 Staggered acupuncture.
[0047] The specific method of laying layer by layer is as follows: a layer of carbon cloth and a layer of mesh tire are laid evenly layer by layer, and the last layer is sealed with carbon cloth. It is required that no wrinkles or accumulation of the carbon cloth and mesh tire occur during the laying process.
[0048] (2) After the needling is completed, demoulding and curing are performed to obtain a sagger preform embryo.
[0049] The curing temperature is 250-300°C.
[0050] The heating time of the curing treatment is 1-3 hours, and the heat preservation time is 4-8 hours, so as to ensure that the interior of the sagger preform embryo is uniformly cured.
[0051] Among them, the cooling method after the solidification treatment is natural cooling to room temperature.
[0052] (3) Densification of the sagger preform embryo by chemical vapor deposition. The density of the sagger preform embryo after densification is 1.2-1.3 g / cm 3 .
[0053] Among them, the temperature of chemical vapor deposition is 1000-1100°C, the heating time is 20-24h, the insulation time is 250-300h, and the cooling time is 28-32h.
[0054] (4) The sagger preform body is subjected to resin impregnation, curing and carbonization treatment. The density of the sagger preform body after treatment is 1.4-1.5g / cm 3 .
[0055] (5) The sagger preform body is graphitized.
[0056] Among them, the temperature of graphitization treatment is 1800-2100°C, the heating time is 20-40h, the insulation time is 5-10h, and the cooling method is furnace cooling.
[0057] (6) Using the silicon carbide mixture, a silicon carbide coating is evenly applied on the surface of the sagger preform embryo, and the coating is vapor deposited to obtain a finished product with a uniform silicon carbide coating on the surface, that is, a carbon-ceramic composite material sagger.
[0058] The silicon carbide mixture is prepared by uniformly mixing silicon carbide particles and epoxy resin in a weight ratio of (0.5-1): (0.5-1).
[0059] Optionally, the particle size of the silicon carbide particles is ≥200 mesh.
[0060] Optionally, the epoxy resin has a carbon residue rate of ≤30% and a viscosity of 100-280 mPa·s.
[0061] Among them, the temperature of the vapor deposition coating is 1000-1100°C, the heating time is 24h, the insulation time is 250-300h, and the cooling time is 32h.
[0062] In a specific embodiment, reference Figure 1 , which is a carbon-ceramic composite material sagger prepared by the preparation method provided in the present application.
[0063] In a specific embodiment, the preparation method provided in the present application specifically comprises the following steps:
[0064] (1) According to the specifications and dimensions of the sagger preform embryo, make the corresponding mold.
[0065] (2) Paste soft foam material on the mold surface.
[0066] (3) Install the mold on the sagger needle machine, first 300-500g / m 2 Plain carbon cloth and 50-200g / m 2 The carbon fiber mesh is pre-compounded and cut into the required shape, laid layer by layer in sequence and needled layer by layer to make a sagger preform. The density of the sagger preform is 0.4-0.6g / cm 3 The order of acupuncture is bottom, bottom arc, straight section and straight section arc. The bottom and bottom arc adopt acupuncture depth of 12-16mm and acupuncture density of 12-25 needles / cm 2 Staggered needling. The needling depth of the straight segment and the straight segment arc is 14-18mm, and the needling density is 12-25 needles / cm 2 Staggered acupuncture.
[0067] (4) After the needle punching is completed, demolding is performed and the preform is cured in a high temperature furnace at 250-300°C. The heating time for the curing treatment is 1 hour and the heat preservation time is 4-8 hours to ensure that the interior of the sagger preform is uniformly cured. The preform is naturally cooled to room temperature to obtain the sagger preform.
[0068] (5) Use a chemical vapor deposition furnace to perform chemical vapor deposition densification on the sagger preform embryo. The temperature of chemical vapor deposition is 1000-1100℃, the heating time is 24h, the insulation time is 250-300h, and the cooling time is 32h. The density of the sagger preform embryo after densification is 1.2-1.3g / cm 3 .
[0069] (6) Use an impregnation furnace and a carbonization furnace to perform resin impregnation, curing and carbonization treatment on the sagger preform. After treatment, the density of the sagger preform reaches 1.4-1.5g / cm 3 .
[0070] (7) The sagger preform body is graphitized in a high-temperature graphitization furnace. The graphitization temperature is 1800-2100°C, the heating time is 20-40h, the heat preservation time is 5-10h, and the cooling method is cooling along with the furnace.
[0071] (8) Machining the sagger preform body to the finished product size.
[0072] (9) Using a silicon carbide mixture to evenly apply a silicon carbide coating on the surface of the sagger preform body. The silicon carbide mixture is prepared by evenly mixing silicon carbide particles and epoxy resin in a volume ratio of 1:1.
[0073] (10) Surface coating treatment is performed using a chemical vapor deposition furnace to perform vapor deposition coating; the temperature of the vapor deposition coating is 1000-1100° C., the heating time is 24 hours, the heat preservation time is 250-300 hours, and the cooling time is 32 hours; a finished product having a uniform silicon carbide coating on the surface is obtained, namely, a carbon-ceramic composite material sagger.
[0074] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application are clearly and completely described below in conjunction with the accompanying drawings. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.
[0075] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0076] The present application is further described in detail below in combination with embodiments, comparative examples, drawings and test results.
[0077] Example
[0078] Example 1
[0079] This embodiment provides a carbon-ceramic composite material sagger. The preparation method of the carbon-ceramic composite material sagger specifically comprises the following steps:
[0080] (1) According to the specifications and dimensions of the sagger preform embryo, make the corresponding mold.
[0081] (2) Paste soft foam material (Eva material) on the surface of the mold.
[0082] (3) Install the mold on the sagger needle machine, first add 200-400g / m 2 Plain carbon cloth and 50~100g / m 2 The carbon fiber mesh is pre-compounded and cut into the required shape, laid layer by layer and needled layer by layer in sequence to make a sagger preform. The density of the sagger preform is 0.4g / cm 3 The order of acupuncture is bottom, bottom arc, straight section and straight section arc. The bottom and bottom arc adopt acupuncture depth of 11-14mm and acupuncture density of 16-20 needles / cm 2 Staggered needling. The needling depth of the straight segment and the straight segment arc is 14-16mm, and the needling density is 18-20 needles / cm 2 Staggered acupuncture.
[0083] (4) After the needle punching is completed, the mold is removed and the preform is cured in a high-temperature furnace at 200-250°C. The heating time for the curing treatment is 1 hour and the heat preservation time is 4-6 hours to ensure that the interior of the sagger preform is uniformly cured. The preform is naturally cooled to room temperature to obtain the sagger preform.
[0084] (5) The sagger preform body is densified by chemical vapor deposition in a chemical vapor deposition furnace. The temperature of chemical vapor deposition is 1100°C, the heating time is 24h, the holding time is 275h, and the cooling time is 32h. The density of the sagger preform body after densification is 1.2g / cm 3 .
[0085] (6) Use an impregnation furnace and a carbonization furnace to perform resin impregnation, curing and carbonization treatment on the sagger preform. After treatment, the density of the sagger preform reaches 1.4 g / cm 3 .
[0086] The specific process is as follows: perform resin pressure impregnation, the impregnation pressure is 3Mpa, the impregnation time is 3h, after impregnation, heat up and pressurize to solidify, the solidification pressure is 2Mpa, the heating time is 10h, the heat preservation time is 2h, and the temperature is lowered before taking out of the furnace. Perform carbonization and take out of the furnace, the carbonization temperature is 1000℃.
[0087] (7) The sagger preform body is graphitized in a high-temperature graphitization furnace. The graphitization temperature is 1900°C, the heating time is 21 hours, the heat preservation time is 7 hours, and the cooling method is cooling along with the furnace.
[0088] (8) Machining the sagger preform body to the finished product size.
[0089] (9) Using a silicon carbide mixture to evenly apply a silicon carbide coating on the surface of the sagger preform body. The silicon carbide mixture is prepared by evenly mixing silicon carbide particles and epoxy resin in a weight ratio of 1:1.
[0090] (10) Using a chemical vapor deposition furnace to carry out surface coating treatment, vapor deposition coating is carried out; the temperature of the vapor deposition coating is 1000-1100° C., the heating time is 24 hours, the heat preservation time is 180-250 hours, and the cooling time is 32 hours; a finished product with a uniform silicon carbide coating on the surface is obtained, that is, a carbon-ceramic composite material sagger is obtained.
[0091] Embodiment 2-10
[0092] Embodiments 2-10 provide a carbon-ceramic composite material sagger respectively. The difference between the preparation method of the carbon-ceramic composite material sagger and that of embodiment 1 is that the density parameters of different preforms are specifically shown in Table 1, and the rest are consistent with embodiment 1.
[0093] Table 1 Parameters of some steps in the preparation methods provided in each embodiment
[0094]
[0095] Comparative Example
[0096] Comparative Example 1
[0097] This comparative example provides a carbon-ceramic composite material sagger. The preparation method of the carbon-ceramic composite material sagger is different from that of Example 1 in that it does not include step (9) of applying a silicon carbide coating and step (10) of vapor deposition of the coating, and the remaining steps are consistent with those of Example 1.
[0098] Comparative Example 2
[0099] This comparative example provides a carbon-ceramic composite material sagger. The difference between the preparation method of the carbon-ceramic composite material sagger and that of Example 1 is that the step (10) of vapor deposition of coating is not included, and the remaining steps are consistent with those of Example 1.
[0100] Comparative Example 3
[0101] This comparative example provides a graphite sagger.
[0102] The preparation method of the graphite sagger is as follows:
[0103] (1) Preparation of substrate: weigh 60 g of graphite powder, 6 g of carbon powder, and 10 g of solid phenolic resin, and mix them in a kneading pot;
[0104] (2) The temperature of the heat preservation box is raised to 80°C, the material kneaded in the kneading pot is placed in the heat preservation box for preheating for 15 minutes, and then pressed by the molding machine;
[0105] (3) The pressed substrate mold is then placed in a furnace for graphitization treatment at a furnace temperature of 1650°C for 18 hours;
[0106] (4) Preparation of spray powder: weigh 60 g of silicon carbide powder, 2 g of nano-silicon dioxide, and 3 g of carbon powder, and mix them evenly to obtain spray powder;
[0107] (5) The substrate is heated to 200° C., and then the spray powder is sprayed on the surface of the substrate by a spray gun to form a coating. The spraying thickness of the coating is 0.05 mm, and a graphite carbon-based sagger is obtained.
[0108] Performance testing
[0109] The compressive strength, bending strength, wear resistance and oxidation resistance of the saggers provided in the above embodiments and comparative examples were tested respectively.
[0110] The specific testing methods are as follows: tensile strength refers to "GB / T 33501-2017 Test method for tensile properties of carbon-carbon composite materials"; flexural strength refers to "GB / T 34559-2017 Test method for compression properties of carbon-carbon composite materials"; friction coefficient refers to "GB / T 10006-2021 Determination of friction coefficient of plastic films and sheets"; antioxidant test method: ablate the sample at 1100°C for 48 hours and detect the weight loss rate.
[0111] The test results are shown in Table 2.
[0112] Table 2 Test results of saggers provided by the embodiments and comparative examples
[0113]
[0114] As can be seen from Table 2, the tensile strength of the sagger provided in the present application can reach above 180 MPa, the bending strength can reach above 110 MPa, the friction coefficient is above 0.3, and the weight loss rate is below 15%, which is superior to the graphite sagger in the related art.
[0115] In addition, the service life of the sagger provided by the present application can reach 20-24 months under a high temperature of more than 1600°C and a micro-oxygen environment (oxygen content below 200ppm). The silicon carbide coating on the surface of the sagger provided by the present application can meet the requirements of long-term rolling friction with metal wheels without shedding bare carbon fiber, effectively protecting the carbon-carbon material from oxidation. In particular, the tensile strength of the sagger provided by the present application can reach more than 180MPa, which meets the requirements of frequent grabbing and handling during use.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a carbon-ceramic composite material sagger, characterized in that: The preparation method specifically comprises the following steps: Based on the mold, the pre-compounded plain carbon cloth and carbon fiber mesh are cut, laid layer by layer, and needled layer by layer to form a sagger preform; the density of the sagger preform is 0.4-0.6g / cm³; the density of the plain carbon cloth is 300-500g / m 2 The density of the carbon fiber mesh is 50-200g / m 2 ; After the needle punching is completed, demoulding and curing treatment are performed to obtain a sagger preform embryo, and the sagger preform embryo is densified by chemical vapor deposition; the density of the sagger preform embryo after densification is 1.2-1.3g / cm³; Continue to perform resin impregnation, curing and carbonization treatment on the sagger preform embryo; after the treatment, the density of the sagger preform embryo is 1.4-1.5g / cm³; Then, the sagger preform embryo is subjected to graphitization treatment; The silicon carbide mixture is used to evenly apply a silicon carbide coating on the surface of the sagger preform embryo, and the coating is vapor deposited to obtain a finished product with a uniform silicon carbide coating on the surface, that is, a carbon-ceramic composite material sagger.
2. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The silicon carbide mixture is prepared by uniformly mixing silicon carbide particles and epoxy resin in a weight ratio of (0.5-1): (0.5-1); Optionally, the particle size of the silicon carbide particles is ≥200 mesh; Optionally, the epoxy resin has a carbon residue rate of ≤30% and a viscosity of 100-280 mPa·s.
3. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The temperature of the vapor deposition coating is 1000-1100° C., and the insulation time is 250-300 hours.
4. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The sequence of acupuncture is bottom, bottom arc, straight section and straight section arc.
5. The method for preparing a carbon-ceramic composite material sagger according to claim 4, characterized in that: The bottom and the bottom arc are needled in an alternating manner with a needle depth of 12-16 mm and a needle density of 12-25 needles / cm².
6. The method for preparing a carbon-ceramic composite material sagger according to claim 4, characterized in that: The straight segment and the straight segment arc are needled in an alternating manner with a needle puncture depth of 14-18 mm and a needle puncture density of 12-25 needles / cm².
7. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The curing treatment temperature is 250-300° C., and the heat preservation time is 4-8 hours.
8. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The temperature of the chemical vapor deposition is 1000-1100° C., and the insulation time is 250-300 hours.
9. The method for preparing a carbon-ceramic composite material sagger according to claim 1, characterized in that: The temperature of the graphitization treatment is 1800-2100° C., and the insulation time is 5-10 hours.
10. A carbon-ceramic composite material sagger prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of C / C-SIC composite with low cost and low density gradient
CN105884389A
C / C-SiC composite material of sandwich structure and preparation method thereof
CN107879758A